PERAN BIDAN DALAM MEMBERIKAN PELAYANAN KONSELING GIZI PADA IBU HAMIL DI PUSKESMAS AMURANG BARAT - Mega Nanda Dahlan, Putri; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: Optimal nutrition during pregnancy has a major impact on maternal health and fetal development. It is hoped that nutritional counseling services by midwives at the West Amurang Community Health Center can increase understanding and practice of healthy nutrition in pregnant women. Objective: This study aims to explore the role of midwives in providing nutritional counseling services to pregnant women at the West Amurang Community Health Center using a cross-sectional quantitative approach. Method: The research design used was quantitative cross-sectional. The sample consisted of 16 pregnant women who actively visited the West Amurang Community Health Center. Data was collected through a questionnaire which included questions about nutritional knowledge and perceptions of the counseling services provided. Results: The results of the analysis show that there is a significant relationship between the role of midwives in nutritional counseling services and nutritional knowledge of pregnant women at the West Amurang Community Health Center (p-value = 0.003). Most pregnant women show an increase in nutritional knowledge after receiving counseling from midwives. Conclusion: This research highlights the important role of midwives in increasing nutritional knowledge of pregnant women through counseling services at the West Amurang Community Health Center. The results showing a significant relationship between the role of midwives and nutritional knowledge emphasize the importance of continuous education for midwives in providing effective and responsive services.